2015
DOI: 10.1109/tim.2015.2434097
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Algorithm for EMG Signal Processing and Muscle Timing Measurement

Abstract: This paper presents a new method for the automated processing of surface electromyography (SEMG) signals, particularly suited for the detection of muscle activation timing. The method has an intermediate level of complexity between simpler (but less performing) and more complex (but in general slower) methods, and is successfully used in the development of biomedical devices for rehabilitation carried out by our group.\ud The method proposed here is based on a statistical approach for threshold computation tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…Therefore, the most popular choice is to use RMS or some variant as the primary metric for determining whether there is a contraction. The general approach is to look at a limited bandwidth of the spectrum to determine the existence of contractions (generally with a lowpass or a band-pass filter) [57]. However, since PLN frequency overlaps with the bandwidth sEMG is most dominant, it can significantly degrade the performance of these metrics.…”
Section: Prior Art and Comparisonsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the most popular choice is to use RMS or some variant as the primary metric for determining whether there is a contraction. The general approach is to look at a limited bandwidth of the spectrum to determine the existence of contractions (generally with a lowpass or a band-pass filter) [57]. However, since PLN frequency overlaps with the bandwidth sEMG is most dominant, it can significantly degrade the performance of these metrics.…”
Section: Prior Art and Comparisonsmentioning
confidence: 99%
“…Another technique is to set the threshold to the RMS of the last contraction and to compare this with the RMS of the incoming frames while incrementally decreasing it with a decay parameter. In [57], the authors calculate the 5% and 95% percentile RMS values and use a convex combination 1 Spectrum Estimation of them as threshold. In [59], the authors propose a peak detection algorithm, where the number of sEMG measurements above a selected threshold are determined to make a decision.…”
Section: Prior Art and Comparisonsmentioning
confidence: 99%
“…The surface electromyography (sEMG) reflects the electrical activity of muscle fibres during contraction, and it has been widely used for intelligent prostheses or exoskeleton robotics control [1,2]. To decode human intentions from sEMG more intuitively, artificial intelligence (AI) can be leveraged in either the classification-based hand gesture recognition [3,4] or regression-based kinematic estimation [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Although it was demonstrated that threshold-based algorithms are less robust in activity recognition rather than machine-learning algorithms [34], it should be underlined that machine-learning algorithms cannot prescind from the training phase and they should be performed for each worker and each industrial workspace, making it difficult to apply these procedures in a real industrial scenario. For this reason, we decided to implement a threshold-based algorithm, also taking into account that this methodology is often used in human motion identification [35][36][37].…”
Section: Threshold-based Algorithm For Counting (Tb)mentioning
confidence: 99%